Determinants of price promotion attractiveness in fast moving consumer goods - Grangeio, Maria Sofia Ravara Cary Frade (2016)
With the growing brand similarity and brand proliferation, the changes in the mass market and in consumer shopping patterns, sales promotions have become one of the main strategies employed by brand managers to boost sales, coming to represent up to three times the expenditures used in advertising. The rise of promotional intensity caught the attention of many scholars who have tried to understand what are the characteristics of a sales promotion that guarantee the best feedback from consumers and the highest purchase intentions. This study compares the effects of several types of price promotions, which vary according to the way price discount is framed, on consumers overall evaluations of the promotion and purchase intentions. This will contribute to the literature since other authors have never focused solely on the framing of price promotion, manipulating other variables, such as different percentages of discount into their studies, at least in the Fast Moving Consumer Goods Industry. It will also contribute by following the works of Lichtenstein et al. (1990), seeing how the authors’ findings on the effects of consumers’ traits on promotions perform in the type of promotions being studied. Results from a quantitative study performed through a questionnaire survey with 222 participants show, however, that consumers’ behavior towards price promotions is significantly more dependent on their personal attitudes and characteristics, namely Brand Preference, Sale Proneness and Value Consciousness, rather than depending on how the promotion is framed, at least when a constant level of price discount is offered.